Minimalist Lifestyle Campaign on Tiktok: An Analysis of Rejection of Postmodernist Society - Dzurrotul Adiba Humaida,; Citra Orwela, (Mediakita, 2024)
This article discusses the minimalist lifestyle campaign on TikTok, an effort to reject the lifestyle of postmodernism society. According to Jean Baudrillard, the lifestyle of postmodernist society is considered to have a consumptive tendency where the value of consumption is more massive than the value of production. This lifestyle requires that in consuming, it is seen not only on the day of use value but also in the fulfillment of signs and symbols. The author uses a qualitative research method, Roland Barthes' theory of semiotic analysis. This article shows that the consumerist lifestyle, identical to postmodernist society, has many detrimental effects on humans, especially the environment. So a campaign was launched by a community account on TikTok for minimalist lifestyle @lyfewithless.community #BelajarJadiMinimalis to mobilize and socialize a Minimalist lifestyle that prioritizes the use value and restores the essence of consumption itself, namely using something because it is needed, not the desire to fulfill certain symbols.